1998
DOI: 10.1136/jms.5.3.120
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis of a national thalassaemia prevention programme in Israel

Abstract: Objective-In Israel (population 5.7 million) there are around 200 known living subjects with thalassaemia major, of whom around 80% are from the northern district. This study aims at examining the costs and benefits of a national screening programme to prevent thalassaemia in Israel. Measurements and main results-The lifetime healthcare costs of caring for a person born with thalassaemia major are $284 154. The costs of the home infusion service (33.1%) actually exceed the costs of the chelating agent itself (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 18 publications
1
45
1
Order By: Relevance
“…40 The benefits of accurate diagnosis of iron deficiency and other hemoglobinopathies -hemoglobin S and β-thalassemia in particular -should also be considered. Costbenefit analyses of β-thalassemia prevention programs in Quebec, 41 Iran, 42 Israel, 43,44 and the United Kingdom 45 have generally confirmed the overall benefits of such programs (i.e., the costs of prevention were lower than the costs of treatment), but the studies did not include α-thalassemia. In low-and middle-income countries, the implementation of such programs could benefit from existing infrastructures (e.g., ongoing screening programs for phenylketonuria or glucose-6-phosphate dehydrogenase deficiency) or could result in an overall improvement in access to health care for local communities.…”
Section: He a Lth A Nd Economic Bur Denmentioning
confidence: 99%
“…40 The benefits of accurate diagnosis of iron deficiency and other hemoglobinopathies -hemoglobin S and β-thalassemia in particular -should also be considered. Costbenefit analyses of β-thalassemia prevention programs in Quebec, 41 Iran, 42 Israel, 43,44 and the United Kingdom 45 have generally confirmed the overall benefits of such programs (i.e., the costs of prevention were lower than the costs of treatment), but the studies did not include α-thalassemia. In low-and middle-income countries, the implementation of such programs could benefit from existing infrastructures (e.g., ongoing screening programs for phenylketonuria or glucose-6-phosphate dehydrogenase deficiency) or could result in an overall improvement in access to health care for local communities.…”
Section: He a Lth A Nd Economic Bur Denmentioning
confidence: 99%
“…Only four studies were identified that contained data related to the costs of infused ICT. [21][22][23][24] On the basis of the literature, a single composite list of cost variables (such as drug, equipment, monitoring toxic effects, and psychotherapist) was created to serve as the basis for the health economics component of the case report form. Frequency of use and unit cost data for each of these variables were identified from the literature, this study, administrative databases, and medical supply catalogues.…”
Section: Annual Costs Of Ictmentioning
confidence: 99%
“…2,3 The lifetime cost of treating a patient with thalassemia major is estimated to be d80 000 (4US$ 110 000) in the United Kingdom 4,5 and US$ 284 154 in Israel. 6 Recent data from the Taiwan Thalassemia Association indicate that more than 400 patients have b-thalassemia major or other transfusion-dependent thalassemias in Taiwan, and their treatment costs account for a considerable percentage of the Taiwan's National Health Insurance expenditure. The pediatric HSCT program started in Taiwan in 1984, when an allogeneic bone marrow transplantation was performed in a patient with bthalassemia major.…”
Section: Introductionmentioning
confidence: 99%